Pengaruh Ukuran Perusahaan, Profitabilitas Dan Leverage Terhadap Perataan Laba Pada Sektor Industri Perbankan - Musdholifah, ; Diana Puspitasari, (Bisnis dan Manajemen, 2009)
Income smoothing is an action that taken by management to decrease reported company profit fluctuation. Income smoothing practice is a phenomena that commonly happens as managements effort to reach certain aims. The purpose of this research is finding out whether there is income smoothing practice in banking industrial sector or not and identifying factors that influence income smoothing. Four factors that includes companys size, profitability, financial leverage and operating leverage will be used to identify factors that influence income smoothing index. There is separation between company that performs income smoothing and not performing income smoothing by using Eckel Index for companies in banking industrial sector that registered in Jakarta Stock Exchange. This research is involving 16 banking companies that registered in Jakarta Stock Exchange by performing 4 years experiment started from 2004 until 2007. The result of the counting with Eckel Index shows that there is 9 companies in banking industrial sector that perform income smoothing practice. The result of univariate and multivariate, in order to find out the influence of each factor, shows that profitability, financial leverage and operating leverage do not influence income smoothing (Sig>0,05) meanwhile companys size has positive influence to income smoothing (Sig